2014
DOI: 10.1111/1440-1681.12283
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a double‐hit murine model of acute respiratory distress syndrome

Abstract: The aim of the present study was to characterize a murine model of acute respiratory distress syndrome (ARDS) abiding by the Berlin definition of human ARDS and guidelines for animal models of ARDS. To this end, C57BL/6NCrl mice were challenged with lipopolysaccharide (LPS; 15 mg/kg, i.p.) followed 18 h later by injection of oleic acid (OA; 0.12 mL/kg, i.v.). Controls received saline injection at both time points. Haemodynamics were monitored continuously. Arterial blood gas analyses were performed just before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
12
0
2
Order By: Relevance
“…This novel finding could suggest an under investigated role for the IL-17-T helper 17 cell pathway during ARDS resolution and stimulate further research (29,30). The report of sRAGE plasma levels in lung injured mice is rather novel (31) and further supports the value of sRAGE as a surrogate marker of lung injury severity in general (10)(11)(12), and of AFC in particular, in both the experimental and clinical settings of ARDS. Because of the evidence that alveolar epithelial type I cells transport sodium and contribute to AFC(32, 33), a marker of AT I cell injury could reflect intact AFC.…”
Section: Levels Of Srage Are Associated With Lung Injury Severitysupporting
confidence: 53%
“…This novel finding could suggest an under investigated role for the IL-17-T helper 17 cell pathway during ARDS resolution and stimulate further research (29,30). The report of sRAGE plasma levels in lung injured mice is rather novel (31) and further supports the value of sRAGE as a surrogate marker of lung injury severity in general (10)(11)(12), and of AFC in particular, in both the experimental and clinical settings of ARDS. Because of the evidence that alveolar epithelial type I cells transport sodium and contribute to AFC(32, 33), a marker of AT I cell injury could reflect intact AFC.…”
Section: Levels Of Srage Are Associated With Lung Injury Severitysupporting
confidence: 53%
“…Also, the overall amount of TNF-α in the lungs was lower than in other experimental settings that applied much more potent triggers of inflammation, such as lipopolysaccharides (LPS). 36 …”
Section: Discussionmentioning
confidence: 99%
“…Research aimed to evaluate new therapeutic options judiciously tailored for effective treatment of ricin-induced pulmonary intoxication, requires the availability of an animal model that lends itself to continuous monitoring of respiratory and hemodynamic parameters. Although recent reports have shown that a mouse model can be utilized for assessment of pulmonary gas exchange and respiratory mechanics following controlled induction of acute respiratory distress syndrome (ARDS; Patel et al, 2012 , Voelker et al, 2014 ), mechanical ventilation and repeated blood sampling could be carried out in mice for only a very short time. These mice model systems are therefore not amenable with the surveillance of progression of ricin pathology where clinical symptoms can be discerned only many hours after exposure to the toxin and death occurs only within several days.…”
Section: Introductionmentioning
confidence: 99%